2018
DOI: 10.1038/s41598-018-34157-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of progressive ankylosis protein (ANKH) in craniometaphyseal dysplasia

Abstract: Mutations in the progressive ankylosis protein (NP_473368, human ANKH) cause craniometaphyseal dysplasia (CMD), characterized by progressive thickening of craniofacial bones and widened metaphyses in long bones. The pathogenesis of CMD remains largely unknown, and treatment for CMD is limited to surgical intervention. We have reported that knock-in mice (AnkKI/KI) carrying a F377del mutation in ANK (NM_020332, mouse ANK) replicate many features of CMD. Interestingly, ablation of the Ank gene in AnkKO/KO mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…P5L and G389R both localised more slowly to the cell membrane, E490del showed some cell membrane localisation but was mostly cytoplasmic and S375del did not at any time. A recent paper on novel mutant ANKH-F377del, also shows evidence of the mutated protein to be dispersed in the cytoplasm 18 . Although we see similar wt.ANKH localisation as reported by Kanaujiya, J. et al 18 and many other non-bone cell lines, we cannot discount the effects that this may be specific to bone.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…P5L and G389R both localised more slowly to the cell membrane, E490del showed some cell membrane localisation but was mostly cytoplasmic and S375del did not at any time. A recent paper on novel mutant ANKH-F377del, also shows evidence of the mutated protein to be dispersed in the cytoplasm 18 . Although we see similar wt.ANKH localisation as reported by Kanaujiya, J. et al 18 and many other non-bone cell lines, we cannot discount the effects that this may be specific to bone.…”
Section: Discussionmentioning
confidence: 95%
“…A recent paper on novel mutant ANKH-F377del, also shows evidence of the mutated protein to be dispersed in the cytoplasm 18 . Although we see similar wt.ANKH localisation as reported by Kanaujiya, J. et al 18 and many other non-bone cell lines, we cannot discount the effects that this may be specific to bone. These very different localisation dynamics, even between mutants causing similar clinical features, highlights the complex and diverse function of ANKH in the pathogenesis of CPPDD and CMD.…”
Section: Discussionmentioning
confidence: 95%
“…( 9 ) We showed that mutant ANK/ANKH protein levels were significantly reduced due to rapid protein degradation whereas the expression of mutant Ank/ANKH mRNA transcripts was comparable to wild‐type Ank/ANKH . ( 5 ) Although Ank KI/KI mice showed a tendency of decreased serum Pi, the difference was not statistically significant in comparison to Ank +/+ mice. ( 10 ) Other Pi regulating hormones such as PTH, 25‐OHD, and intact and cleaved FGF23, were unexpectedly normal in the CMD mouse model as well as in patients with CMD.…”
Section: Introductionmentioning
confidence: 93%
“…(3,4) ANK is a transmembrane protein localized on plasma membranes, endoplasmic reticulum, and Golgi apparatus. (5,6) ANKH/ANK is highly conserved within vertebrates and ubiquitously expressed in skeletal and nonskeletal tissues to regulate or prevent tissue mineralization by transporting intracellular pyrophosphate (PPi) to the extracellular matrix. (3,7) In vitro experiments in oocytes showed that CMD mutant ANK transports less PPi.…”
Section: Introductionmentioning
confidence: 99%
“…ankylosis progressive homolog (anKH), an amino acid of 492 base pairs in length, is a multichannel transmembrane protein that transports intracellular pyrophosphate (PPi) to the extracellular milieu (13). Extracellular PPi was discovered to be a regulator of pathological calcification and a potential inhibitor of calcium phosphate mineralization (14)(15)(16). ANKH is the human homolog of the murine ANK gene (15).…”
Section: Introductionmentioning
confidence: 99%